The Improving English Speaking Skills Through Tour Guiding Practice at Tundrumbaho Megalith Stone, Idanotae, South Nias - Harefa , Afore Tahir; Hia, Zakiah Tafonao; Mendrofa, Rezeki; Waruwu, Jethrialdo (Teaching English and Language Learning English Journal, 2026)
English speaking skills play a crucial role in cultural tourism settings where tour guides serve as mediators between visitors and local heritage. However, in many cultural tourism sites, including Tundrumbaho Megalith Stone in South Nias, limited English proficiency and the lack of contextual learning materials hinder effective tour guiding practices. This study aims to develop an English tour guide book based on the historical and cultural heritage of Tundrumbaho as a medium to support future speaking practice. Employing a Research and Development (R&D) approach in its initial stages, the research focused on needs analysis, cultural documentation, and preliminary product design. Data were collected through semi-structured interviews with traditional custodians and community members, as well as field observations at the Tundrumbaho site. The findings reveal that the site contains rich historical narratives related to ancestral leadership, megalithic traditions, and symbolic cultural values, yet these narratives are not communicated effectively to foreign visitors due to linguistic limitations. The needs analysis indicates the necessity for contextual English materials that integrate cultural content, tourism vocabulary, and communicative functions relevant to tour guiding tasks. The study concludes that the development of an English tour guide book is feasible and strategically important for enhancing speaking competence, supporting cultural tourism, and preserving local heritage. Further stages of R&D involving expert validation and product testing are recommended to measure the guidebook’s effectiveness in improving English speaking skills.